Kingdom of the Netherlands-Netherlands : Publication of Financial Sector Assessment Program Documentation: Detailed Assessment of Observance on Basel Core Principles for Effective Banking Supervision (BCP). (IMF Staff Country Reports; Country Report ;, 2011)
The major reforms undertaken in the Netherlands with the adoption of the Twin Peaks regulatory structure have ensured that the recommendations from the Basel Core Principles assessment have been acted upon. The legal and regulatory framework for banking supervision conforms to internationally accepted minimum standards. Executive Directors recommend that supervision has to be more 'intrusive and conclusive,' and encourage greater use of formal enforcement powers. However, it is recommended that the allocation of supervisory resources according to the potential systemic impact of regulated firms be evaluated.